Comparative Characteristics of Bone Marrow - Lyudmila P. Nikolaeva (International Journal of Advanced Science and Technology, 2020)
Introduction: Cellular therapy is becoming increasingly important in medicine. It is based on bone marrow functions. The study of bone marrow is acute. We can use stem cells as efficiently as possible when we study the bone marrow completely.